Preserving Traditions as a Perspective for the Future? The Integration History of German Expellees in the Context of Current Discourses on Diversity - Kasten, Tilman (Ethnographica et Folkloristica Carpathica, 2023)
Diversity is a central keyword of our time that has found its way into the academic discussion of (historical) migration phenomena and their consequences. This also applies to the history of the forced migration of the German-speaking population from Eastern Europe as a result of the Second World War, which confronted both the refugees and expellees as well as the “host societies” with major challenges including those concerning “integration”. Based on a critical reading of a historically informed contribution to the debate on the evaluation of the integration history of the German expellees in the Federal Republic of Germany, the article reflects on the question of the extent to which orientation points for current debates on a social self-understanding under the guise of diversity can be derived from this history.